NURSING IMPLEMENTATION IN CONTROLONG COGNITIVE AND PSYCHOMOTOR CAPABILITIES OF HALLUCINATORY PATIENTS IN KALAWA ATEI MENTAL HOSPITAL OF PALANGKA RAYA - Maria Magdalena Purba (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Hallucination is one of the symptoms of mental disorders in individuals that are characterized by sensory changes in perception, feeling a false sensory in the form of sound, vision, taste, touch and smell that is felt by the patient, but actually nothing. Hallucinatory can affect to the patient behaviors and sometime can endanger others. By implementing nursing of cognitive abilities and psychomotor abilities be expected to control hallucinatory among patients. This study aims to determine the implementation of cognitive abilities and psychomotor abilities in controlling hallucinatory in Atei Kalawa Menta Hospital, Palangkaraya. Methods: This study was a quantitative study. There were 32 respondents that recruited in this study used purposive sampling methods. The inclusion criteria for this study were patients in Atei Kalawa Mental Hospital who had aged 20-56 and dignosed for schizophrenia. The univariate analysis was used to describe the descriptive statistic. Results: Implementing cognitive and psychomotor abilities towards patients with hallucinatory can decrease the hallucinatory among 17 patients (53.1%) and improve the ability from 19 patients (59.4%) to communicate with others, to do schedule activities, and to follow the medication. Conclusion: By implementing cognitive and psychomotor towards patients who had hallucinatory can bring positive impact in their treatment. It is recommended for health providers to implementing cognitive and psychomotor towards patients who faced hallucinatory.